Implementation of students’ communicative problems in social, educational and professional, and sociocultural spheres (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
In the article main tasks of teaching Ukrainian as a foreign language are determined: foreign students’ formation of communicative and language, linguistic, discursive, sociocultural and pragmatic competences; development of skills of interethnic communication; upbringing of respect to the Ukrainian nation. The reasons are laid out which can be an obstacle in the process of mastering a language, and prevent reaching the goal of teaching: the absence of natural language environment; artificial motivation for mastering a foreign language; non-frequent variation of verbal examples. It is recommended in the educational process to form the real need to get a peculiar extra linguistic result that is connected with personal goals and motives of foreign interlocutors.The requirements to a modern lecturer are specified: constant study and understanding individual peculiarities of presenters of any nationality, especially temperament, features of character, views, habits; diagnosis and correction of the level of personal traits being formed (world view, motivation, interests, personality orientation, life plans); encouragement of every student to reasonable activity with constantly growing requirements; identification and overcoming the causes which do not let a student to achieve personal development. It is emphasized that language proficiency includes learning complex of codes of the peculiar language and the rules of their use for forming thoughts, rendering the content and comprehension of the expressed intentions.
Keywords: a foreign interlocutor; communicative need; language competence; educational verbal situation